Analysis of The Determinants of Decisions of Underemployed Female Workers in The Informal Sector in Denpasar City - Anak Agung Istri Diah Nindyaswari; Made Heny Urmila Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The city of Denpasar is in first place regarding the number of the workforce, but not all residents have normal working hours so their productivity has not been utilized optimally. The main objective of this research is to analyze the influence of age , level of education, age of last child, traditional and religious activities simultaneously and partially on the decision of female workers in the informal sector to choose to be underemployed in Denpasar City. The data used in this research is primary data , namely by conducting structured interviews with respondents . The research population is all female informal sector workers who are underemployed in Denpasar City, totaling 13,062 people. The sampling method used is quota sampling . In this research, the number of samples determined to be studied was 100 underemployed female workers . The results of multiple linear regression analysis show that age, level of education, age of last child, traditional activities and religion simultaneously have a significant influence on the decision of female workers in the informal sector to work and become underemployed. Age partially has a positive effect, while education level, age of the last child, and traditional and religious activities partially have a negative effect on the decision of women in the informal sector to choose to be underemployed in Denpasar City.